Absorption avoided resonance crossing of hybridization of silicon nanoparticles and gold nanoantennas - Jhen-Hong Yang; Min-Wen Yu; Kuo-Ping Chen (Scientific Reports, 2019)
Abstract The near-field coupling between a high-refractive-index nanoparticle and gold nanoantennas is investigated theoretically. The absorption enhancement and also avoided resonance crossing in the absorption cross section spectra were observed with the hybridization system due to the coupling between the localized surface plasmon resonance of the gold nanoantennas and the magnetic dipole resonance of the silicon nanoparticle. By controlling the nanoparticle size or the separation distance, the near-field coupling can be tuned from the weak to the strong regime.